314 mm2 Hexagonal Double-Sided Spiral Silicon Drift Detector for Soft X-Ray Detection Based on Ultra-Pure High Resistance Silicon - Liu, Manwen; Li, Zheng; Deng, Zhi; He, Li; Xiong, Bo; Li, Yuyun; Feng, Mingfu; Tang, Lipeng; Cheng, Min (Frontiers in Materials, 2021)
An X-ray pulsar is a remnant of massive star evolution, collapse, and supernova explosions. It has an extremely stable spin cycle and is known as the most accurate astronomical clock in the natural world. It presents high-precision navigational information, such as the location, speed, time, and attitude, which are used in deep space exploration and interstellar flight, such as the X-ray Pulsar Navigation (XPNAV). However, the energy of the X-ray from the pulsar is very low and its signal is very weak; this X-ray is known as the soft X-ray. In the low and medium energy radiation spectroscopy, the semiconductor detectors, especially the Silicon Drift Detectors (SDD), achieve the best energy resolution. In this study, a 314 mm2 and a 600 mm2 double-sided spiral hexagonal silicon drift detector (DSSH-SDD) single cell for the pulsar soft X-ray detection is analyzed based on ultra-pure high-resistance silicon. The DSSH-SDD device is fabricated using ultra-pure high-resistivity silicon substrates patterned with ion-implanted electrodes. This study proposes a model capable of reaching a large area of 314 mm2 or 600 mm2 single cell and maintaining an optimal drift electric field. The design, modeling, 3D simulation, and the fabrication of the model are performed to analyze the physical performance of the DSSH-SDD. The electrical characteristics of the as-processed SDD chips, including leakage current, anode capacitance, and the spiral resistor current under the positive and negative biases are measured; and the energy resolution test is performed at the Tsinghua University. The energy resolution is an important indicator of the detector and is often expressed by full width at half maximum (FWHM). The results obtained in this study can be applied in the future for novel, flexible, large-area, high-resolution ionizing radiation detection systems capable of providing quantitative and real-time information of the relative position of spacecraft and pulsars through the pulsar X-ray radiation.